Comparative Characteristics of Teaching Children and Youth in Ukraine and Japan - Kuchai, Tetiana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article presents a comparative analysis, found similarities and differences in the development of student learning and teacher training at universities in Japan and Ukraine. The origins of Japanese economic miracle are particularly suited to the training and education of the younger generation, combining western trends with the traditional humanistic educational principles. The Japanese education system, like Ukrainian, has undergone transformation towards humanistic many difficulties due to historical conditions and characteristics of the national mentality. Comparative analysis of the education system in Japan and Ukraine showed similar approaches in the educational process in schools: the structure of schools (primary, basic, senior), the operation of private schools, although there is a difference in the period of training; the use of credit- modular technology that promotes democratization of education; organizational forms of the educational process for the preparation of teachers (lectures, seminars, practical and so on.); Graduate School offers training both competition and on contract basis in government educational institutions; there are p